Sensitivity enhancement of the tactile sensor based on hydrothermally grown ZnO nanorods modified by catalytic Au nanoparticles - Yurong Liu; Lin Zhu; Yinxue Xiang; Ming Li (Materials Research Express, 2022)
Flexible piezoelectric tactile sensor with transverse planar electrodes based on hydrothermally grown ZnO nanorods (ZnO NRs) was presented by using polydimethylsiloxane (PDMS) as flexible substrate and packaging material. The effects of the content of gold nanoparticles (AuNPs) added into the precursor solution on the structural morphology of ZnO NRs and on the piezoelectric properties of the ZnO NRs tactile sensor were investigated. Tactile sensors show a linear piezoelectric response in the pressure range of 0–1 N, and the sensor for the precursor solution with AuNPs of 100 μ l shows a high sensitivity of 1.42 V N ^−1 due to the large aspect ratio of the ZnO NRs, indicating that a small amount of AuNPs addition can optimize the structural morphology of ZnO NRs and thus improve the piezoelectric response of the sensor. Meanwhile, the sensor is employed to monitor human information in real-time such as bending/stretching motion of finger and distinguish various objects.